Determinants of University Students’ Motivation to Use Educational Technology: A Path Analytic Study - Khasawneh, Samer (Jordan Journal of Educational Sciences, 2005)
The objective of the present study was to model and test the extent to which previous success, educational technology (ET) anxiety, and instructor-provided training influenced ET efficacy beliefs, and subsequent motivation to use ET in the university classroom. Social Learning Theory (Bandura, 1982) was used as the theoretical framework to develop hypotheses and to test relationships. The results, based on a sample of 282 students, supported the hypothesized causal model. Previous success had a positive direct effect on self-efficacy (β = 0.10) and negative effect on anxiety (β = - 0.23). Training had a negative direct effect on anxiety (β = - 0.41) and positive effect on self-efficacy (β = 0.43). Anxiety had a negative direct effect on self-efficacy (β = -0.20). Finally, self-efficacy had a positive direct effect on motivation (β = .17). This study provides some evidence that this model is helpful in determining students’ motivation to use ET.